The Practice of Translanguaging Pedagogy Approach In EFL Classroom - Datungsolang, Fadila Amalia; Habibie, Alvons; Nabu, Andiani Rezkita; Hasan, Jhems Richard; Helingo, Adimawati (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
In the last decade, the application of translanguaging in language teaching has attracted the attention of researchers and educational practitioners. Although many studies have explored the benefits of Translanguaging, a gap remains in the literature on how Translanguaging is effectively applied in the context of learning English as a foreign language (EFL) in Islamic higher Education. This study explores the practice of the translanguaging pedagogy approach in English as a Foreign Language (EFL) classes at the English Education Department of IAIN Sultan Amai Gorontalo. This research employed a qualitative approach with a case study design, focusing on first-year students and English lecturers in the English Education Department at IAIN Sultan Amai Gorontalo. The participants included 25 students (six males and 19 females) and two English lecturers. The results revealed that translanguaging was frequently used by both lecturers and students across five observed sessions in various English courses, including Literal Inferential Reading, Speaking for Formal Interaction, and English Basic Grammar. A total of 300 translanguaging instances were recorded, with Insertion (24.67%), Intra-sentential (23%), and Inter-sentential (18.67%) being the most common types, followed by Entire (17.33%) and Congruent Lexicalization (16.33%). This helps improve their understanding of the material being taught and gives them greater confidence in learning the target language.Keywords: Translanguaging, Approach, EFL Classroom